2008
DOI: 10.1007/s00018-008-8049-7
|View full text |Cite
|
Sign up to set email alerts
|

Recent progress in understanding the diversity of the human ov-serpin/clade B serpin family

Abstract: The inhibitory mechanism against proteases is important in the maintenance of homeostasis or health in the body. The human ovalbumin serpin (ov-serpin)/clade B serpin family is one group of the human serpins, a family of serine protease inhibitors. They have acquired diversity in the profiles of target proteases, inhibitory mechanisms, and localization patterns during their evolution. Most serpins target serine proteases, however, some ov-serpins target only cysteine proteases or both serine and cysteine prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
66
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(69 citation statements)
references
References 97 publications
3
66
0
Order By: Relevance
“…These complexes were suggested to contain a serine protease that is activated during this process, but this activity was never identified. Nevertheless, these observations raise the hypothesis that some ov-serpins may share a common function in controlling cell death, and that their specific physiological roles may have been obscured as a result of redundancy (14,41). Although it remains to be further investigated, our observations that PAI-2 and TG2 interact in cells, and mediate a common antiapoptotic response, suggest that these unconventional antiapoptotic factors participate in a posttranslational mechanism that controls caspase-3 activation.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…These complexes were suggested to contain a serine protease that is activated during this process, but this activity was never identified. Nevertheless, these observations raise the hypothesis that some ov-serpins may share a common function in controlling cell death, and that their specific physiological roles may have been obscured as a result of redundancy (14,41). Although it remains to be further investigated, our observations that PAI-2 and TG2 interact in cells, and mediate a common antiapoptotic response, suggest that these unconventional antiapoptotic factors participate in a posttranslational mechanism that controls caspase-3 activation.…”
Section: Discussionmentioning
confidence: 82%
“…Although it remains to be determined whether TG2 can also crosslink other caspases, including caspase-8, this observation provides a missing molecular link that explains the observation made more than a decade ago that the C-D interhelical domain or C-D loop of PAI-2, a conserved protein binding domain among ovserpin family members (14), was essential for the antiapoptotic function of PAI-2 in TNF-stimulated cells (22). It was postulated that an interaction between the C-D loop and unknown proteins was likely to be important for resistance to apoptosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several proteolytic enzyme systems, including plasminogen activators, matrix metalloproteinases (MMPs) and other enzymes, are considered to be intimately involved in the invasion and metastasis of tumor cells (1,2). The serine protease urokinase-type of plasminogen activator (uPA) together with the uPA receptor (uPAR), which plays an essential role in the conversion of plasminogen to active plasmin, have been implicated in facilitating pericellular proteolysis and oncogenic signal transduction in cancer cells (3,4). The proteolytic activity of uPAR-associated uPA is blocked by serine protease inhibitors such as maspin and PAI-1,2 (plasminogen activator inhibitor-1), leading to internalization of the trimeric complex, degradation of uPA and recycling of uPAR (5)(6)(7)(8)(9) Invasion and metastasis are the most crucial characteristics of malignant tumors.…”
Section: Introductionmentioning
confidence: 99%
“…Genomic cloning and sequencing revealed that they are 91% identical at the amino acid level, but show distinct properties and substrates (5) and their physiological roles are poorly understood.…”
Section: Introductionmentioning
confidence: 99%